Penelitian Hubungan Pengetahuan Perawat Dengan Penanganan Awal Pasien Trauma Dada Di Ugd - Agatha Marella Thoms (Observasi : Jurnal Publikasi Ilmu Psikologi, 2023)
Trauma requires immediate and appropriate treatment. Because if the handling is not right or wrong it will result in further complications, such as infection, damage to nerves and blood vessels so that it can result in further soft tissue damage. Knowledge is the result of knowing and this has happened after a person runs his senses on a certain object. This sensory process occurs based on the five senses of every human being, namely the sense of sight, hearing, smell, taste and touch (Notoadmodjo, 2014).